The Trickle-Down Effect of Territorial Behavior: A Moderated Mediation Model - Li, Yi; Weng, Haolin; Zhu, Ting; Li, Na (Frontiers in Psychology, 2021)
The present research seeks to explore how and when leader territorial behavior trickles down to the follower. Relying on social information processing theory, we hypothesize that territorial behavior has a trickle-down effect from leader to follower and perceived insider status mediates the relationship between leader territorial behavior and follower territorial behavior. Competition climate is supposed to strengthen the effect of leader territorial behavior on perceived insider status. In a sample of 252 employees from 65 teams in Chinese enterprises, we tested the hypotheses by using Mplus. The results suggest that leader territorial behavior is positively related to follower territorial behavior and that follower perceived insider status significantly mediates the relationship. Moreover, competition climate strengthens the negative relationship between leader territorial behavior and perceived insider status as well as the indirect effect of leader territorial behavior on follower territorial behavior via perceived insider status. Theoretical and practical implications are further discussed.